Diseño y construcción de un tablero didáctico para prácticas de conexión de transformadores. - Huaca Buri, Ángel Polívio (2016)
Electricity is the "engine" that drives the development of the industry worldwide, motors, generators and transformers constitute fundamental components for the manufacture of processed materials. The proper functioning of these teams depends on the generation of wealth in many nations, why companies look for qualified technical personnel to ensure proper preventive and corrective maintenance of all equipment and tools used in their companies. Have deep technical knowledge of the operation and establishment of these teams ensures that institutions, factories, hospitals, etc. are not in the need to paralyze their daily activities, thus avoiding many economic losses. This research work aims at the implementation of a module for connecting transformers practices in the electronics laboratory, which will train the student in the knowledge of the operation, constitution and connections, the same is provided with three reducers single-phase transformers voltage, with its primary and secondary windings fully identified and a source phase input to perform all possible connection.